Hardness, VSM, cyclic voltammetric and DFT studies of Cesium Sulphate-doped TGS crystals - Blessy, S. Jerin; Jeyakumar, H. Johnson; Juliana, S. Gracelin; Selvarajan, P.; Prabhu, A. Antony Muthu (Physics and Chemistry of Solid State, 2024)
The creation of capacitors, transducers, sensors, and infrared detectors utilise the nonlinear, ferroelectric triglycine sulphate (TGS) crystal. Cesium sulphate is incorporated into the lattice of TGS crystal to change its characteristics. Cesium sulfate-doped triglycine sulphate (CSTGS) single crystals were produced using a solution approach and a slow evaporation process. The title crystal was studied by single crystal XRD, FTIR, hardness, VSM, cyclic voltammetric and density functional theoretical (DFT) studies and the results are discussed in this paper.